In Search of Terms: An Empirical Approach to Lexicography - Josselin-Leray, Amelie; Roberts, Roda (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn the framework of a more general research project on the place and role of terms (i.e. lexical items belonging to languages for special purposes) in general dictionaries, an empirical study was undertaken with different categories of users of such dictionaries - language experts, scientists and the general public. The purpose of the study was to investigate the use they make of documentary and dictionary resources to find the terms they need. This paper will present some of the results of the survey conducted and examine the impact that these results could have on the practice of lexicography.